Milk intake is inversely related to body mass index and body fat in girls - Abreu, S (2012)
Dairy foods comprise a range of products with varying nutritional content. The intake of dairy products (DPs) has been shown to have beneficial effects on body weight and body fat. This study aimed to examine the independent association between DP intake, body mass index (BMI), and percentage body fat (%BF) in adolescents. A cross-sectional, school-based study was conducted with 1,001 adolescents (418 boys), ages 15-18 years, from the Azorean Archipelago, Portugal. Anthropometric measurements were recorded (weight and height), and %BF was assessed using bioelectric impedance analysis. Adolescent food intake was measured using a self-administered, semiquantitative food frequency questionnaire. Data were analyzed separately for girls and boys, and separate multiple linear regression analysis was used to estimate the association between total DP, milk, yogurt, and cheese intake, BMI, and %BF, adjusting for potential confounders. For boys and girls, respectively, total DP consumption was 2.6 +/- 1.9 and 2.9 +/- 2.5 servings/day (P = 0.004), while milk consumption was 1.7 +/- 1.4 and 2.0 +/- 1.7 servings/day (P = 0.001), yogurt consumption was 0.5 +/- 0.6 and 0.4 +/- 0.7 servings/day (P = 0.247), and cheese consumption was 0.4 +/- 0.6 and 0.5 +/- 0.8 servings/day (P = 0.081). After adjusting for age, birth weight, energy intake, protein, total fat, sugar, dietary fiber, total calcium intake, low-energy reporters, parental education, pubertal stage, and physical activity, only milk intake was negatively associated with BMI and %BF in girls (respectively, girls: beta = -0.167, P = 0.013; boys: beta = -0.019, P = 0.824 and girls: beta = -0.143, P = 0.030; boys: beta = -0.051, P = 0.548). Conclusion: We found an inverse association between milk intake and both BMI and %BF only in girls.